Forced Vibration Numerical Analysis of Reticulate Systems by Dynamic Finite Element Method - Passoli, A. Olivier; Olodo, E. T. Emmanuel; DOKO, KOUANDETÉ VALERY; Alé, Georges; ADJOVI, EDMOND CODJO (My University, 2019)
This work is devoted to forced vibration numerical analysis of reticulate bar systems. The dynamic finite element method was used for determination of frequencies, displacement amplitudes, rotation angles and the dynamic effort factors. By this method the components of the dynamic rigidity matrix and inertia matrix depend on applied external excitation frequency. Obtained results are compared with those calculated by the classical finite element method as well as by analytical method. It is shown that the dynamic finite element allows for exact solutions to the problems in forced vibration of structures. Accuracy of dynamic finite element solution is verified through obtaining analytical solutions on simple systems. In case of complex systems where analytical calculations are complicated the dynamic finite element can become a universal tool for dynamic analysis.
Keywords: forced vibrations; numerical analysis; reticulate systems